Northeasters of Tripura State - BANERJEE , A. K.; DATTA, D. K. (MAUSAM, 1975)
A study of thundersqualls over Agartala during pre-monsoon months for a period of 12 years (1962-73) has revealed that frequency of squalls from N-E quadrant is significantly greater than, those from N-W quadrant each month. As such, the term ‘Nor’ wester’ assigned to the thundersqualls of Bengal and adjoining as eastern regions may not perhaps be an appropriate qualifying term for the thundersqualls which affect Tripura state. The average speed associated with, squalls, from N-W quadrant was however found to be greater than those from N.E but the average rainfall associated with the latter was significantly greater than that associated with the former. Thunderstorms from N-E quadrant are the principal contributors to the pre-monsoon rain in Tripura.